2008 Computers in Cardiology 2008
DOI: 10.1109/cic.2008.4749209
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional device for cardiologic telemedicine and diagnostic holter

Abstract: Although different systems are available on the market to record ECG and to send it to an analisys station, there is still demand for a more vesatile, easy to use device that shorten the time the diagnosis is available, avoiding the patient to move to a healthcare center: the purpose of our work was to validate a solution that fullfil this requirement. Twenty family doctors and two cardiologists were involved in the evaluation of the whole solution and 400 exams were performed. The results showed that the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the future it will be the starting point for many specialized clinical and non clinical applications, such as chronic care management [3,4], telemedicine application [5,6,7], patients tracking [8,9,10], technology management [11] and drugs smart administration [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In the future it will be the starting point for many specialized clinical and non clinical applications, such as chronic care management [3,4], telemedicine application [5,6,7], patients tracking [8,9,10], technology management [11] and drugs smart administration [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…All physiological signs and critical indices were transmitted to a patient's phone through bluetooth and further to a doctor's phone through global communication technology. Belardinelli et al, 2008) The system offered a high standard of healthcare with cost reduction. The limitations were system performance and information security during transmission.…”
Section: Related Literaturementioning
confidence: 99%
“…A Belardinelli et al (2008)have suggested a more versatile, easy to use device that shortens the diagnosis time, avoids the patient to move to a healthcare center .The device was well tolerated by patients and the work flow allures the practitioners for the combination of its simplicity and effectiveness in reducing the time to reach the diagnosis, although a remarkable number of cardiac traces were not good enough to formulate a diagnosis, mainly due to contact loss in the patient's electrical circuit. All the causes of bad electrical connections were investigated and corrective measures were taken to improve the number of good quality signals.…”
Section: Related Literaturementioning
confidence: 99%